Efektivitas Audit Kinerja dalam Meningkatkan Kinerja Pelayanan dan Perbaikan Kebijakan Pemerintah pada Sektor Kesehatan - Raja Mendrofa; Roma Rejeki Hotminar Sitompul; Adi Syaputra Ritonga; Gabrielle Simanjuntak; M. Irsan Nasution (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The health sector is a crucial component of public services that requires strict oversight based on economic, efficiency, and effectiveness (3E) aspects. Performance auditing serves as an independent evaluation tool to map the achievements of government health programs and ensure state financial accountability. This literature review aims to analyze in depth the effectiveness of performance audit implementation on operational service quality and macro policy reform in the health sector. The research method used is a qualitative descriptive approach with a literature study design that adapts the principles of the PRISMA framework. Digital articles were searched on Google Scholar, ResearchGate, and ScienceDirect databases for national and international scientific publications within the 2023–2026 timeframe. The analysis results are synthesized into a thematic literature matrix encompassing 20 selected articles, then contextualized through an analysis of fiscal efficiency in post-pandemic health spending and operational case studies in Indonesia. Research findings indicate that at the micro-operational level, performance auditing significantly contributes to drug supply chain improvements, IT governance optimization, and service time reduction. At the macro level, performance auditing plays a vital role in evaluating the reallocation of post-pandemic health budgets, detecting idle crisis medical assets, and redirecting curative spending back toward sustainable preventive programs. However, its role in transforming comprehensive structural policy remains at a moderate level due to weak follow-up on recommendations, the absence of strict fiscal penalty sanctions, and the existence of medical competence gaps (skill-gaps) among public auditors.